FORMULASI SEDIAAN LULUR KRIM AMPAS KEDELAI PUTIH DAN AMPAS KOPI ARABIKA - Surya Ningsi; Faridha Yenny Nonci; Rifqiyati Sam (Universitas Islam Negeri Alauddin Makassar, 2015)
The formulation of herbal preparations have been done scrub cream white soybean dregs and arabica coffee dregs using a variation of the type of emulsifier, the nonionic surfactant (tween 80 and span 80) and a anionic surfactant (sodium lauryl sulfate). This study aims to determine the type of emulsifier which has good physical stability. Test stability scrub cream dosage is determined based on observations of organoleptic (color, smell and shape), creaming, viscosity, size of the dispersed drops, pH and phase inversion on the condition before and after accelerated storage at a temperature of 5oC and 35oC. Statistical analysis showed that the RAK emulsifier no significant differences on viscosity scrub cream before and after the storage accelerated and does not give any influence on organoleptic, the size of the dispersed drops, the pH before and after accelerated storage. The results of the study showed no creaming and inverse phase with all the scrub cream, so that all can be categorized as scrub cream with good stability.